Antidepressant-like effects of sodium butyrate and its possible mechanisms of action in mice exposed to chronic unpredictable mild stress. (8th April 2016) - Sun, Jing; Wang, Fangyan; Hong, Guangliang; Pang, Mengqi; Xu, Hailing; Li, Haixiao; Tian, Feng; Fang, Renchi; Yao, Ye; Liu, Jiaming
Highlights: NaB has beneficial effects on mice exposed to chronic unpredictable mild stress. NaB reverses the depressive behaviors caused by chronic unpredictable mild stress. NaB increase 5-HT concentration in the hippocampus. NaB increases BDNF expression in the hippocampus. NaB up-regulates Occludin and ZO-1 levels, suggesting it restores BBB impairments. Abstract: Sodium butyrate (NaB) has exhibited neuroprotective activity. This study aimed to explore that NaB exerts beneficial effects on chronic unpredictable mild stress (CUMS)-induced depression-like behaviors and its possible mechanisms. The behavioral tests including sucrose preference test (SPT), open field test (OFT), tail suspension test (TST) and forced swimming test (FST) were to evaluate the antidepressant effects of NaB. Then changes of Nissl's body in the hippocampus, brain serotonin (5-HT) concentration, brain-derived neurotrophic factor (BDNF) and tight junctions (TJs) proteins level were assessed to explore the antidepressant mechanisms. Our results showed that CUMS caused significant depression-like behaviors, neuropathological changes, and decreased brain 5-HT concentration, TJs protein levels and BDNF expression in the hippocampus. However, NaB treatment significantly ameliorated behavioral deficits of the CUMS-induced mice, increased 5-HT concentration, increased BDNF expression, and up-regulated Occludin and zonula occludens-1(ZO-1) protein levels in the hippocampus, which demonstrated that NaB could partially restore CUMS-induced blood–brain barrier (BBB) impairments. Besides, the pathologic changes were alleviated. In conclusion, these results demonstrated that NaB significantly improved depression-like behaviors in CUMS-induced mice and its antidepressant actions might be related with, at least in part, the increasing brain 5-HT concentration and BDNF expression and restoring BBB impairments.